South American National Contributions to Knowledge of the Effects of Endocrine Disrupting Chemicals in Wild Animals: Current and Future Directions - Rojas-Hucks, Sylvia; Rodriguez-Jorquera, Ignacio A.; Nimpstch, Jorge; Bahamonde, Paulina; Benavides, Julio A.; Chiang, Gustavo; Pulgar, Jose; Galban-Malagon, Cristobal J. (My University, 2022)
Human pressure due to industrial and agricultural development has resulted in a biodiversity crisis. Environmental pollution is one of its drivers, including contamination of wildlife by chemicals emitted into the air, soil, and water. Chemicals released into the environment, even at low concentrations, may pose a negative effect on organisms. These chemicals might modify the synthesis, metabolism, and mode of action of hormones. This can lead to failures in reproduction, growth, and development of organisms potentially impacting their fitness. In this review, we focused on assessing the current knowledge on concentrations and possible effects of endocrine disruptor chemicals (metals, persistent organic pollutants, and others) in studies performed in South America, with findings at reproductive and thyroid levels. Our literature search revealed that most studies have focused on measuring the concentrations of compounds that act as endocrine disruptors in animals at the systemic level. However, few studies have evaluated the effects at a reproductive level, while information at thyroid disorders is scarce. Most studies have been conducted in fish by researchers from Brazil, Argentina, Chile, and Colombia. Comparison of results across studies is difficult due to the lack of standardization of units in the reported data. Future studies should prioritize research on emergent contaminants, evaluate effects on native species and the use of current available methods such as the OMICs. Additionally, there is a primary focus on organisms related to aquatic environments, and those inhabiting terrestrial environments are scarce or nonexistent. Finally, we highlight a lack of funding at a national level in the reviewed topic that may influence the observed low scientific productivity in several countries, which is often negatively associated with their percentage of protected areas.
Keywords: south america; wildlife species; endocrine disruptors; trace elements; organic compounds; metals; ecotoxicology